HUBUNGAN ANTARA KUALITAS PELAYANAN DAN HARGA DENGAN KEPUASAN PELANGGAN PADA BENGKEL SUZUKI SUN MOTOR MATRAMAN - Imelda Aprileny (Jurnal Ekonomi, 2016)
The purpose of this study was to determine how closely the relationship between service quality and price to customer satisfaction in the garage SUN MOTOR Matraman. The strategy used in this study is an associative strategy. The method used in this research is a survey as part of a descriptive research with quantitative approach. The population in this study is that customers who have subscribed during the years 2014-2015 and has been visited 5 times. Based on existing data, obtained the number of customers who have been 5 times a year during 2014 to 2015 was 114 people. Based on calculations using the formula slovin, obtained the total sample of 89 respondents.Based on the results of research to test the correlation coefficient, obtained by the partial correlation coefficient and regression. From the analysis of partial correlation coefficient, partial correlation value X1 to Y of 0.472, which means the relationship of service quality and customer satisfaction, are moderate and the direction that is positive assuming constant prices. While the partial correlation value X2 to Y of 0.530, which means that the relationship of price to customer satisfaction, are and the direction that is positive with regards the quality of service constant. The value multiple correlation coefficient of 0.952, showing the relationship between service quality and price to customer satisfaction is very strong with a relationship that is positive or unidirectional, meaning if the quality of service and price can be supplied with either, then customer satisfaction will increase, and vice versa if quality of service and price can not be given properly, then customer satisfaction will decrease. From the results of partial hypothesis testing, obtained P-value variables X1 0,000, smaller than the real level or 0.000 <0.05. Therefore, it can be deduced Ho refused or Ha accepted, meaning partially contained significant positive correlation variables of service quality and customer satisfaction. While the P-value of 0.000 X2, smaller than the real level or 0.000 <0.05. Therefore, it can be deduced Ho refused or Ha accepted, meaning partially contained significant positive correlation with the price variable customer satisfaction. From the results of hypothesis testing simultaneously, gained significance F 0,000, is smaller than the real level or 0.000 <0.05. Thus, it can be deduced Ho refused or Ha accepted, meaning there is simultaneously a significant positive relationship between service quality and price to customer satisfaction.